P161 A comparative study of childhood-onset SLE with adult-onset patients: a single centre study. (26th April 2021) - Morton, Neil T; Rutter-Locher, Zoe; Durrani, Maumar; Sangle, Shirish; Wilkinson, Nick; D'Cruz, David
Abstract: Background/Aims Childhood-onset SLE (cSLE) was once associated with significant mortality but 5-year survival rates have now improved significantly. We retrospectively compared the clinical features and outcomes of cSLE patients with an adult-onset SLE (aSLE) group. Methods We retrospectively studied data from 30 patients from our cSLE patients (onset before age 16) compared with 65 aSLE randomly selected in a 2:1 ratio, from our Lupus clinic patients fulfilling the 1997 ACR SLE criteria. Data regarding ethnicity, age of onset, family history, serology, complications, medications and outcomes were recorded. Results Of cSLE patients 24 were female and 6 male (F:M ratio 4:1), with 16 patients (53%) Afro-Caribbean, 8 Caucasian, 5 Asian and 1 of mixed ethnicity. In the aSLE group, 60 patients were female and 5 male (ratio 9:1), with 29 (44%) Afro-Caribbean, 13 Asian, 21 Caucasian and 2 of mixed ethnicity. Median age at disease onset was 14 years (10-16) in cSLE and 29 years (17-50) in aSLE. A positive family history of SLE was seen in 37% (11/30) of cSLE patients compared to 11% (7/65) of aSLE [p = 0.003]. There was no difference in family history of other autoimmune rheumatic diseases (10% vs 14% [p = 0.57]). Table 1 shows frequency of different autoantibodies, with anti-dsDNA and anti-cardiolipin antibodies significantly more frequent in the cSLE group [p = 0.017, p = 0.016 respectively]. Lupus nephritis appears to be more common in cSLE but not significantly (80% renal involvement vs 69% aSLE).There was no difference between involvement of chest, haematological, VTE or APS. Standard of care treatment was used in both groups, including oral prednisolone (>80% patients), anti-malarial and immunosuppressive medications. Renal flares were significantly more frequent in cSLE (23% vs 8%, [p = 0.027]). Of those deceased, only 1 was directly due to SLE. Conclusion More cSLE patients had a positive SLE family history and had higher anti-dsDNA antibody positivity compared to aSLE. Renal involvement was observed more commonly in cSLE than aSLE patients but was not statistically significant. Our results suggest that the cSLE cohort have a higher prevalence of specific lupus serology and a positive family history of SLE which may point towards more aggressive disease. Disclosure N.T. Morton: None. Z. Rutter-Locher: None. M. Durrani: None. S. Sangle: None. N. Wilkinson: None. D. D'Cruz: None.